The Role of Effective Supply Chain Practices on Firm Performance: Mediating Role of Organizational Culture - AHMAD, DR. MUHAMMAD AZEEM; HASHMI, DR. ARSHIA (The journal of contemporary issues in business and government, 2021)
The management of supply chain practices is the essential element for high organizational performance and captures the focus of regulators and recent studies. Thus, the current study examines the impact of supply chain practices such as supplier relationship, customer relationship, and lean manufacturing on the performance of manufacturing companies in Pakistan. This research also investigates the mediating role of organizational culture among the relationships of the supplier relationship, customer relationship, lean manufacturing, and performance of manufacturing companies in Pakistan. This study has followed the quantitative approach of data collection and used the questionnaires for this purpose and also used the smart-PLS for analysis purposes. The results exposed that supplier relationship, customer relationship, and lean manufacturing have a positive association with the performance of manufacturing companies. The findings also indicated that organizational culture positively mediates the relationships among the supplier relationship, customer relationship, lean manufacturing, and performance of manufacturing companies in Pakistan. This study will help the policymakers while formulating the policies related to the supply chain and organizational performance.